Neural Nets and Chaotic Carriers - Whittle, Peter (London : I C P, 2010)
Neural Nets and Chaotic Carriers develops rational principles for the design of associative memories, with a view to applying these principles to models with irregularly oscillatory operation so evident in biological neural systems, and necessitated by the meaninglessness of absolute signal levels.Design is based on the criterion that an associative memory must be able to cope with (3z(Bfading data(3y(B, i.e., to form an inference from the data even as its memory of that data degrades. The resultant net shows striking biological parallels. When these principles are combined with the Freeman specification of a neural oscillator, some remarkable effects emerge. For example, the commonly-observed phenomenon of neuronal bursting appears, with gamma-range oscillation modulated by a low-frequency square-wave oscillation (the (3z(Bescapement oscillation(3y(B). Bridging studies and new results of artificial and biological neural networks, the book has a strong research character. It is, on the other hand, accessible to non-specialists for its concise exposition on the basics.s
Appendix 213-218p.; References 219-224p.; Index 225-230p.
Keywords: Artificial neural networks; Associative and storage memories; Computer engineering; Osillatory operation; Computer science